Monetary and financial cooperation in Latin America and regional asymmetries that impact regional integration - Nunes, Rodolfo Vieira (Cadernos do Desenvolvimento, 2022)
This article analyzes the prospects for monetary and financial cooperation in Latin America, as the integration process returns to the discussions due to the latest global crises. The concepts of regional integration, monetary and financial cooperation, and regional asymmetries are presented; from this theoretical-conceptual discussion, the article seeks to present which are the asymmetries that affect the process of monetary and financial integration. Through this literature review and the theory of optimal monetary areas (TAMO), we seek to understand how Latin America is positioned in relation to monetary and financial integration. It follows that monetary and financial cooperation is sometimes seen as a means of fostering integration, but also as a proposal to provide long-term resources and as a source of foreign exchange liquidity for countries. Thus, there are indications that the economies of the region do not have the necessary conditions for regional integration.